Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:(6x-5)+(-7x+2)
1 Remove parentheses.
6x-5-7x+2
2 Collect like terms.
(6x-7x)+(-5+2)
3 Simplify.
-x-3
_____________________________
1 Remove parentheses.
6x-5+7x-2
6x−5+7x−2
2 Collect like terms.
(6x+7x)+(-5-2)
3 Simplify.
13x-7
Hope this helps
-Tobie the dog <3
☆Answer :
- A)
6x - 5 + (-7x + 2) = ...
= 6x - 5 - 7x + 2
= (6x - 7x) + (-5 - 2)
= -x - 7
[tex]\:[/tex]
- B)
6x - 5 - (-7x + 2) = ...
= 6x - 5 + 7x + 2
= (6x + 7x) + (-5 + 2)
= 13x - 3
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.